An abstract model for parallel computations: Gandy's thesis[a]. - Sieg, Wilfried; Byrnes, John (Monist, 1999)
Comments on the claim that any discrete deterministic mechanical device must satisfy the restrictive principles of local causation and unique assembly or `Gandy's Thesis'. Analysis of the notion of machine computation; Determinisrtic calculations; Physical considerations constraining machine computations; Principles to obey in parallel computations.